Wideband transmit-array antenna design with dual-layer ultrathin Huygens’ meta-surface for vehicular sensing and communication - Wang, Ping (2023)
This article proposes a wideband high-gain transmitarray (TA) antenna for vehicular sensing and communication, which employs a dual-layer ultrathin Huygens’ meta-surface (HMS). It consists of a 33 × 33 HMS unit cells-based TA, a feeder horn, and a three-dimensional printed fixture to hold them. Each HMS unit cell has two identical metal patterns (MPs) of two symmetrical U-shaped patches and one H-shaped patch, which are distributed on both surfaces of the ultrathin substrate. A pair of top U-shaped patches form the first single-wavelength loop mode, and another pair of bottom U-shaped patches forms the second single-wavelength loop mode. Due to the different phases of the incident waves on the top and bottom U-shaped patches, the two loop modes are generated at different frequencies. A third half-wavelength dipole mode is provided by the H-shaped patch. The three modes correspond to three different frequencies, forming a wide transmission frequency band. Three near-unity transmission peaks are yielded to ensure high and stable aperture efficiency (AE). As well, the transmission phase of the HMS unit cell varies with geometric dimensions, and five unit cell types are quantized to obtain 360° phase range with a low loss of less than 2.6 dB. To verify the design concept, a prototype is fabricated. Measurements show a 3-dB gain bandwidth of 17.9%, a maximum gain of 30.5 dBi at 26.2 GHz, and a high AE of 41.9%. It has unidirectional radiation pattern while reducing backlobe.